2011
DOI: 10.1103/physreve.83.066315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impurities in the description of surface nanobubbles: Role of nonidealities in the surface layer

Abstract: In a recent study [S. Das, J. H. Snoeijer, and D. Lohse, Phys. Rev. E 82, 056310 (2010)], we provided quantitative demonstration of the conjecture [W. A. Ducker, Langmuir 25, 8907 (2009)] that the presence of impurities at the surface layer (or the air-water interface) of surface nanobubbles can substantially lower the gas-side contact angle and the Laplace pressure of the nanobubbles. Through an analytical model for any general air-water interface without nonideality effects, we showed that a large concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The blockage effect of the contaminations on the gas exchange was not considered by Das, Snoeijer, and Lohse (2010). Later Das (2011) showed that even small surface concentrations of the surfactants have relatively large effect on the effective surface tension and the contact angle. (ii) Further evidence against the conjecture that the contamination theory of Ducker (2009) was provided by Zhang, Uddin et al (2012) who washed away potential impermeable materials with various surfactants.…”
Section: B Contamination Theorymentioning
confidence: 99%
“…The blockage effect of the contaminations on the gas exchange was not considered by Das, Snoeijer, and Lohse (2010). Later Das (2011) showed that even small surface concentrations of the surfactants have relatively large effect on the effective surface tension and the contact angle. (ii) Further evidence against the conjecture that the contamination theory of Ducker (2009) was provided by Zhang, Uddin et al (2012) who washed away potential impermeable materials with various surfactants.…”
Section: B Contamination Theorymentioning
confidence: 99%
“…Surface tension is notoriously sensitive to the presence of contaminants (see, e.g. [14,15]). All the force related results are anyway normalized with respect to surface tension.…”
Section: External Curvature Radiusmentioning
confidence: 99%
“…Surface tension is notoriously sensitive to the presence of contaminants (see, e.g. [39,40]). All the force related results are any way normalized with respect to surface tension.…”
Section: Experimental Conditions and Techniquesmentioning
confidence: 99%